The Role of Principal Visionary Leadership in The 21st Century - Atria liyustari; Syabrina Yunera (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
The 21st century is marked by rapid social, technological, and cultural changes, demanding a comprehensive transformation in the world of education. In this context, visionary leadership of school principals becomes a key element in building adaptive, innovative, and competitive educational institutions. This article aims to examine the strategic role of visionary school leadership in facing the challenges of the 21st century, as well as to formulate implementable strategies that can be applied in educational institutions. The method used is a literature review by examining 25 relevant national and international articles. The study results show that visionary school principals are not only tasked with formulating a transformative vision but also serve as the driving force behind a culture of innovation, digital technology integration, and multi-party collaboration. This article offers a 5K approach—Commitment, Collaboration, Contextualization of vision, Digital capabilities, and Adaptive leadership—as a concrete action framework. The implications of this study provide policy and practice directions for the development of relevant educational leadership in the era of digital transformation.